Identification of MC4R gene and its association with body weight and body size in Kebumen Ongole Grade cattle - Maharani, D.; Fathoni, A.; Sumadi, S.; Hartatik, T.; Khusnudin, M. (Diponegoro University, 2018)
MC4R gene is known as an important candidate gene for the growth trait. The purpose of this research was to identify the MC4R gene in Kebumen Ongole grade cattle and examine its association with growth traits. Data of birth weight (BW), weaning weight (WW), birth body length (BBL), birth chest circumference (BCC), birth shoulder height (BSH), weaning body length (WBL), weaning chest circumference(WCC), weaning shoulder height (WSH) and average daily gain (ADG) were collected and used for analysis of MC4R gene. Sixty blood samples were collected for DNA isolation and PCR amplification. The single nucleotide polymorphisms (SNP) g.1133 C>G was used for genotyping by using PCR-RFLP methods. The frequenciy of G allele (0.59) was greater than C allele (0.41). The highest genotype frequencies have been detected in CG heterozygote animals (0.52) followed by GG (0.33) and CC (0.15) in homozygote animals. The results of Pearson ‘s Chi-square test indicated that the population was not deviate (P>0.05) from the Hardy-Weinberg equilibrium (HWE). The SNP g. 1133 C>G of MC4R gene indicated affecting high birth body length with GG genotype (P<0.05). In conclusion, the SNP g. 1133 C>G may can be a marker for birth body length of calf selection.